A new sensitive method for the simultaneous chromatographic separation and tandem mass spectrometry detection of anticoccidials, including highly polar compounds, in environmental waters - Coxon, Catherine; Gill, Laurence (Elsevier, 2020)
A sensitive and selective method was developed and validated for the determination of 26 anticoccidial compounds (six ionophores and twenty chemical coccidiostats) in surface and groundwater samples at parts-per-quadrillion (pg L−1) to parts-per-trillion (ng L−1) levels by ultra-high performance liquid chromatography with tandem mass spectrometry detection (UHPLC–MS/MS). A range of different analytical columns and mobile phase compositions were evaluated to enhance selectivity and retention of a number of highly polar and basic anticoccidials along with other non-polar coccidiostats. A combined separation, including these problematic polar compounds, was achieved on a phenyl-hexyl column, by binary gradient elution with water/acetonitrile using ammonium formate and formic acid as additives. The anticoccidial residues were extracted from raw, unfiltered, water samples (250 mL) using polymeric divinylbenzene solid phase extraction (SPE) cartridges, with subsequent elution (methanol:acetonitrile:ethyl acetate, 40:40:20, v/v) and concentration prior to determination. The method recovery (at a concentration representative of realistic expected environmental water concentrations based on literature review) ranged from 81% to 105%. The method was successfully validated for 26 anticoccidials, at four concentration levels, in accordance to Commission Decision 2002/657/EC and SANTE/11813/2017 guidelines. Trueness and precision, under within-laboratory reproducibility conditions, ranged from 88% to 111% and 0.9% to 10.3% respectively.
PUBLISHED
Keywords: Chemical coccidiostats; Ionophores; Environmental water; SPE; UHPLC–MS/MS; Smart & Sustainable Planet; WATER QUALITY; emerging organic contaminants; veterinary pharmaceuticals